Evaluation of androgens in the scalp hair and plasma of patients with male-pattern baldness before and after finasteride administration - Ryu, HK; Kim, KM; Yoo, EA; Sim, WY; Chung, BC (WILEY, 2006)
Background Finasteride, a competitive inhibitor of the enzyme 5 alpha-reductase II, is widely used as a medical treatment for patients with male-pattern baldness (MPB), which is affected by the distribution of androgenic steroids. It is also notable that the androgenic effect in MPB is different for each region of the head. Objectives To study the effect of the drug finasteride, we quantified androgenic steroids in the vertex and occipital scalp hair and in the plasma of patients with MPB. Methods The patients with MPB, aged 23-52 years, were treated with finasteride 1 mg daily for 5 months. The hair and plasma samples were hydrolysed, extracted with n-pentane, and derivatized with MSTFA : NH4I : DTE (1000:4:5, v/w/w). We analysed the concentrations of dihydrotestosterone (DHT) and testosterone (T) in the hair and plasma using gas chromatography-mass spectrometry (GC-MS). Results In the hair, the ratio of DHT/T was decreased in the vertex scalp hair after the individual received finasteride (P < 0.005). However, we found no significant difference in the ratio of DHT/T in the occipital scalp hair before and after individuals received finasteride. Like the results in the vertex scalp hair, the ratio of DHT/T in the plasma was remarkably decreased after finasteride administration (P < 0.001). Conclusions This study supports the effect of finasteride in patients with MPB by examining the decreased level of DHT/T in scalp hair and in plasma. Thus, in view of the androgenic effect in the different hair regions, the vertex scalp hair plays a more important role for patients with MPB treated with finasteride than does the occipital hair.
Keywords: 5-ALPHA-REDUCTASE INHIBITORS; MEN; TESTOSTERONE; SERUM; DIHYDROTESTOSTERONE; GROWTH